Identifying areas for improving management accounting tools in the food industry - Amirgaliyeva, Aigul; Kaliyeva, Yelena; Kadyrova, Korlan; Nurpeisova, Nazym; Bolshekbaeva, Karlygash; Beisekova, Perizat (Eastern-European Journal of Enterprise Technologies, 2025)
The object of the research is the individual elements of management accounting in the food industry. The study examines the key challenges faced by food industry organizations, which operate under the influence of numerous diverse factors and have their own industry-specific characteristics. This necessitates the use of modern administrative tools and unconventional solutions based on management accounting principles. Exploring the capabilities of the food industry management accounting system, it was found that the final stage can be extended to obtain data that enable cash flow monitoring, net profit assessment, and the identification of key allocation directions. The findings highlight the need to implement the direct costing system in the country's food industry, as it best aligns with the operational specifics of these production sectors. This approach optimizes the tax burden on enterprises by focusing on variable costs, which are particularly significant in the food industry. The adoption of ERP systems, big data analytics, artificial intelligence, and accounting methods such as ABC costing, target costing, and standard costing enables more precise cost allocation, efficient capacity utilization, and real-time resource management. This contributes to increased profitability and competitiveness of food industry enterprises. The industry-specific features of management accounting in the food sector are closely linked to production structure analysis, accounting for seasonal fluctuations, utilization of average annual capacity, and tracking specific costs such as quality control and compliance expenses